Tonga : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
KEY ISSUES Context: Tonga's economy is rebounding, partially owing to a recovery in agricultural exports. The outlook for tourism is also improving. The reconstruction from a recent cyclone is expected to lead to both a temporary boost to growth and additional financing needs. Risks to the inflation outlook and the external position are low. Fiscal Policy: The projected fiscal cost relating to the cyclone will be largely met by confirmed funding mainly from donor agencies. In the near term, the authorities should focus on reconstruction activities, while a medium-term fiscal strategy should aim at gradually stabilizing and then reducing the debt-to-GDP ratio, in order to improve Tonga's moderate risk of debt distress. This will require careful execution of investments related to the 2019 South Pacific Games. Monetary Policy: The deleveraging cycle of the Tongan banks appears to be ending, and thus National Reserve Bank of Tonga should prepare to gradually withdraw liquidity and tighten monetary conditions once the current signs of a recovery of credit growth are confirmed. The authorities plan to lower the cost of credit through supportive credit policies, including by commercializing the Tonga Development Bank. The successful implementation of such plan requires sound safeguards, including a robust governance structure and firm risk management and accountability frameworks. Structural Policy: Structural reforms to facilitate the functioning of credit markets need to be implemented with renewed vigor. The authorities' intention to gradually phase out existing ad hoc tax incentives is well placed. The promotion of foreign direct investments should focus on business-enabling structural reforms, while the use of tax incentives should be minimized and well targeted.